Green Synthesis and Characterisation of Gold Nanoparticles Using Averrhoa Bilimbi Leaf and Its Anti-Inflammatory and Anti-Microbial Activity - LAKSHMIPRABHA, J.; ROY, ANITHA; RAJESHKUMAR, S. (The journal of contemporary issues in business and government, 2020)
Green synthesis of gold nanoparticles is a method which employs an environment friendly synthesis of nanoparticles with plant extracts and has gained importance over the recent years due to its reduced toxicity. The aim of the present study was to synthesize gold nanoparticles using Averrhoa bilimbi leaf extract and to evaluate its anti-inflammatory activity and anti-microbial activity after characterisation using Transmission Electron Microscopy (TEM). The gold nanoparticles were synthesised using Averrhoa bilimbi leaf extract. The synthesised gold nanoparticles were confirmed by using UV-Visible spectroscopy. The morphology of the Averrhoa bilimbi mediated gold nanoparticles was analysed using TEM. The green synthesised gold nanoparticles were further evaluated for its anti-inflammatory and anti-microbial activities . Visual observation showed colour change from golden yellow to dark red indicating the formation of spherical gold nanoparticles of average size ranging between 4- 40nm. UV-Visible spectroscopy showed a peak between 500-550 nm at 14thh which indicated the presence of gold nanoparticles. The nanoparticles showed potent anti-inflammatory activity at minimal concentration when compared to diclofenac sodium and potent antimicrobial activity against C. albicans in comparison with E. faecalis and S. mutans. The present study, conclude that the green synthesis of gold nanoparticles is an effective, easy, affordable way to synthesize gold nanoparticles of high reaction rate for various biological purposes.